Six‐month outcome after transcatheter edge‐to‐edge repair of severe tricuspid regurgitation in patients with heart failure. (6th February 2018) - Orban, Mathias; Besler, Christian; Braun, Daniel; Nabauer, Michael; Zimmer, Marion; Orban, Martin; Noack, Thilo; Mehilli, Julinda; Hagl, Christian; Seeburger, Joerg; Borger, Michael; Linke, Axel; et al.
Abstract : Aims: Severe tricuspid regurgitation (TR) is common in patients with right‐sided heart failure (HF) and causes substantial morbidity and mortality. Treatment options beyond medical therapy are limited for high‐risk patients. Transcatheter edge‐to‐edge tricuspid valve (TV) repair showed procedural safety and short‐term efficacy. Impact on mid‐term outcome is unclear. This dual‐centre observational study evaluates the mid‐term safety, efficacy and clinical outcome after edge‐to‐edge TV repair for severe TR in patients with HF. Methods and results: Overall, 50 patients with right‐sided HF and severe TR were treated with the transcatheter edge‐to‐edge repair technique; 14 patients were treated for isolated TR and 36 patients for combined mitral regurgitation (MR) and TR. At 6‐month follow‐up (available for 98% of patients), a persistent reduction of at least one echocardiographic TR grade was achieved in 90% of patients and New York Heart Association class improved in 79% of patients. The 6‐minute walk distance increased by 44% (+84 m, P < 0.001), the median N‐terminal pro‐B‐type natriuretic peptide decreased by 30% (from 3625 to 2526 pg/mL, P = 0.002), and the quality of life score improved by 16% (decrease of 6 points in the Minnesota Living with Heart Failure Questionnaire score, P = 0.056). The improvements were comparable in patients undergoing isolated TR or combined MR and TR treatment. During follow‐up, 8 patients died, 14 were hospitalized for worsening of HF, 2 underwent TV surgery, and 2 received a second TV clip procedure. Conclusions: Transcatheter edge‐to‐edge TV repair for severe TR is safe and effective in reducing TR. It appears to be associated with improved clinical outcome in the majority of patients.